Increase in anti-apoptotic molecules, nucleolin, and heat shock protein 70, against upregulated LRRK2 kinase activity. Issue 5 (3rd September 2018) - Jang, Jihoon; Oh, Hakjin; Nam, Daleum; Seol, Wongi; Seo, Mi Kyoung; Park, Sung Woo; Kim, Hyung Gun; Seo, Hyemyung; Son, Ilhong; Ho, Dong Hwan
ABSTRACT: Leucine-rich repeat kinase 2 (LRRK2) is involved in Parkinson's disease (PD) pathology. A previous study showed that rotenone treatment induced apoptosis, mitochondrial damage, and nucleolar disruption via up-regulated LRRK2 kinase activity, and these effects were rescued by an LRRK2 kinase inhibitor. Heat-shock protein 70 (Hsp70) is an anti-oxidative stress chaperone, and overexpression of Hsp70 enhanced tolerance to rotenone. Nucleolin (NCL) is a component of the nucleolus; overexpression of NCL reduced cellular vulnerability to rotenone. Thus, we hypothesized that rotenone-induced LRRK2 activity would promote changes in neuronal Hsp70 and NCL expressions. Moreover, LRRK2 G2019S, the most prevalent LRRK2 pathogenic mutant with increased kinase activity, could induce changes in Hsp70 and NCL expression. Rotenone treatment of differentiated SH-SY5Y (dSY5Y) cells increased LRKK2 levels and kinase activity, including phospho-S935-LRRK2, phospho-S1292-LRRK2, and the phospho-moesin/moesin ratio, in a dose-dependent manner. Neuronal toxicity and the elevation of cleaved poly (ADP-ribose) polymerase, NCL, and Hsp70 were increased by rotenone. To validate the induction of NCL and Hsp70 expression in response to rotenone, cycloheximide (CHX), a protein synthesis blocker, was administered with rotenone. Post-rotenone increased NCL and Hsp70 expression was repressed by CHX; whereas, rotenone-induced kinase activity and apoptotic toxicity remained unchanged. Transient expression of G2019S in dSY5Y increased the NCL and Hsp70 levels, while administration of a kinase inhibitor diminished these changes. Similar results were observed in rat primary neurons after rotenone treatment or G2019S transfection. Brains from G2019S-transgenic mice also showed increased NCL and Hsp70 levels. Accordingly, LRRK2 kinase inhibition might prevent oxidative stress-mediated PD progression. Abbreviations: 6-OHDA: 6-hydroxydopamine; CHX: cycloheximide; dSY5Y: differentiated SH-SY5Y; g2019S tg: g2019S transgenic mouse; GSK/A-KI: GSK2578215A kinase inhibitor; HSP70: heat shock protein 70; LDH: lactose dehydrogenase; LRRK2: leucine rich-repeat kinase 2; MPTP: 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine; myc-GS LRRK2: myc-tagged g2019S LRRK2; NCL: nucleolin; PARP: poly(ADP-ribose) polymerase; PD: Parkinson's disease; PINK1: PTEN-induced putative kinase 1; pmoesin: phosphorylated moesin at t558; ROS: reactive oxygen species GRAPHICAL ABSTRACT: